(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2022)
Considering the potential health hazardous effects, the distribution and deposition of heavy metals and trace elements including Mn, Fe, Cu, Zn, Cd, Cr, and Pb in different tissues (skin, brain, liver, meat, and bone) of broiler and layer chickens, their feeds, litter, and eggs were analyzed using atomic absorption spectrophotometer (AAS) after nitric/perchloric acid digestion. The samples for this study were taken from four poultry industries located at Sreepur upazila of Gazipur district of Bangladesh. The observed levels of heavy metals and trace element contents in different studied samples were to be in the range of 0.143±0.001 to 7.324±0.004 mg/kg for Mn, below the detection limit (BDL) to 324.43±0.003 mg/kg for Fe, 0.451±0.002 to 4.329±0.005 mg/kg for Cu, 0.014±0.001 to 7.413±0.003 mg/kg for Zn, 0.082±0.002 to 7.806±0.002 mg/kg for Cr, 0.112±0.002 to 1.581±0.002 mg/kg for Cd, and BDL to 34.775±0.004 mg/kg for Pb. Although some elements were found at a lower concentration in feed samples, they were found at a higher level in various parts of the examined chickens, eggs, and litter which may be resulted from other sources such as drinking water, soil, and the surrounding environment of the poultry industries. The brain contained a maximum amount of Cd, Cr, and Pb in comparison to other studied tissues of poultry. Most of the chicken body parts showed an excess level of Cr than the recommended guidelines. The Cu and Zn contents were usual in studied egg samples, whereas Mn, Fe, Cd, Cr, and Pb were found higher than their tolerance limits which are highly alarming for public health and demand regular governance and monitoring. Asian Australas. J. Biosci. Biotechnol. 2021, 6 (3), 128-141